Lower mortality is observed among low birth weight young infants who have received home-based care by female community health volunteers in rural Nepal - Dinesh Neupane; Penny Dawson; Robin Houston; Liladhar Dhakal; Jaganath Sharma; KC Gargi; Christina Lagos; Vishnu Khanal; Shiva Raj Mishra; Per Kallestrup (BMC, 2017)
Abstract Background There has been little success in attempts to reduce the proportion of births with low birth weight (LBW). However, deaths associated with LBW may be prevented with extra attention to warmth, feeding, and prevention or early treatment of infections. There are few studies on this in Nepal and in many other developing countries. This is a cohort study to evaluate the risk of deaths among LBW infants who received FCHV follow up visit for home-based care compared to those who did not receive in Rural Nepal. Methods A cohort study design was used with data from the Morang Innovative Neonatal Intervention (MINI) program in Nepal. Relative Risk (RR) is calculated to compare LBW neonates who received FCHV follow up visit as compared to LBW neonates who did not receive visit. Results Out of 51,853 newborn infants recorded in the MINI database, 2229 LBW neonates were included in the analysis. The proportion of deaths among those who received FCHV follow up visit and those who did not receive were 2% (95% CI: 1%; 2%) and 11% (95% CI: 6%; 18%) respectively(P < 0.001). The relative risk of death in LBW infants who received FCHV follow up visit was 84% less as compared to LBW infants who did not receive (RR = 0·16; 95% CI: 0·09, 0·29). Conclusion The current study indicates that to save the lives of LBW young infants simple home-based measures implemented through trained health volunteers within the existing government health system may be effective when technically more sophisticated measures such as tertiary health centers, pediatricians, and expensive technology are limited.